2022
DOI: 10.1007/s00330-022-08930-0
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an ultrasound-based prediction model for differentiating between malignant and benign solid pancreatic lesions

Abstract: Objective To identify the diagnostic ability of precontrast and contrast-enhanced ultrasound (CEUS) in differentiating between malignant and benign solid pancreatic lesions (MSPLs and BSPLs) and to develop an easy-to-use diagnostic nomogram. Materials and methods This study was approved by the institutional review board. Patients with pathologically confirmed solid pancreatic lesions were enrolled from one tertiary medical centre from March 2011 to June 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Huang et al analyzed five different CEUS patterns in a CEUS-based nomogram for malignant and benign solid pancreatic lesions. Hypoenhancement in the venous phase was a feature of malignant lesions [89]. It should be noted that this does not seem to be true for intrapancreatic RCC metastases [83,86].…”
Section: Hyperenhancement Inhomogeneous Pa Ernmentioning
confidence: 99%
“…Huang et al analyzed five different CEUS patterns in a CEUS-based nomogram for malignant and benign solid pancreatic lesions. Hypoenhancement in the venous phase was a feature of malignant lesions [89]. It should be noted that this does not seem to be true for intrapancreatic RCC metastases [83,86].…”
Section: Hyperenhancement Inhomogeneous Pa Ernmentioning
confidence: 99%
“…Previous studies have confirmed that the CEUS enhancement and wash-out patterns can effectively differentiate the solid pancreatic tumors [ 14 17 ]. Huang et al [ 16 ] reported that hypo-enhancement in all phases, hyper-enhancement/iso-enhancement followed by washout on CEUS, an ill-defined border, and a dilated main pancreatic duct were independent risk factors for malignant solid pancreatic lesions (MSPL). The nomogram based on deep learning CEUS and clinical factors could serve as a preoperative, noninvasive, and precise evaluation tool to differentiate aggressive and non-aggressive pancreatic neuroendocrine neoplasms [ 17 ].…”
Section: Introductionmentioning
confidence: 99%